Jobs and safety: A social exchange perspective in explaining safety citizenship behaviors and safety violations. (December 2018) - Laurent, Julie; Chmiel, Nik; Hansez, Isabelle
Highlights: The job demands-resources model can explain safety performance behaviors. The impact of job resources on participation can illustrate reciprocation processes. Perceived management commitment to safety reflects instrumental processes. Abstract: In this paper we extend the Job Demands Resources model of situational and routine safety violations proposed by Hansez and Chmiel (2010) to incorporate contextual variables (participation in voluntary safety activities and the perspective employees take on whether such activities are part of their job or not). We draw on a Social Exchange Theory (SET) perspective of job resources (JR) to test important new relationships between safety specific and non-safety specific processes. We build on prior observations that safety participation (SP) predicts lower safety violations, and that employee perspectives on such discretionary activities predicts their discretionary safety behavior (Neal and Griffin, 2006; Chmiel et al., 2017). We adopt a SET perspective for two reasons. First, because SP is discretionary, it can be reciprocated by employees, and reciprocation is central to SET perspectives (Blau, 1964; Eisenberger et al, 1986). Second, because Hansez & Chmiel showed that a safety-specific variable, Perceived Management Commitment to Safety (PMCS), explained additional variance in safety violations over the JDR model. PMCS can be regarded as reflecting anticipated rewards for behaving safely, another key psychological process connected to SET (Blau, 1964; Emerson, 1976). Structural analyses used a sample of 1922 workers from a Belgium steel company. Results add to the understanding of processes predicting safety violations, suggesting that JR promote, not just engagement and anticipatory rewards for acting safely, but important additional reciprocation processes deserving further exploration.